Breaking the Fundamental Limitations of Nanoscale Ferroelectric Characterization: Non‐Contact Heterodyne Electrostrain Force Microscopy. Issue 11 (7th October 2021) - Zeng, Qibin; Huang, Qicheng; Wang, Hongli; Li, Caiwen; Fan, Zhen; Chen, Deyang; Cheng, Yuan; Zeng, Kaiyang
Abstract: Perceiving nanoscale ferroelectric phenomena from real space is of great importance for elucidating underlying ferroelectric physics. During the past decades, nanoscale ferroelectric characterization has mainly relied on the Piezoresponse Force Microscopy (PFM) invented in 1992, however, the fundamental limitations of PFM have made the nanoscale ferroelectric studies encounter significant bottlenecks. In this study, a high‐resolution non‐contact ferroelectric measurement, named Non‐Contact Heterodyne Electrostrain Force Microscopy (NC‐HEsFM), is introduced. It is demonstrated that NC‐HEsFM can operate on multiple eigenmodes to perform ideal high‐resolution ferroelectric domain mapping, standard ferroelectric hysteresis loop measurement, and controllable domain manipulation. By using a quartz tuning fork (QTF) sensor, multi‐frequency operation, and heterodyne detection schemes, NC‐HEsFM achieves a real non‐contact yet non‐destructive ferroelectric characterization with negligible electrostatic force effect and hence breaks the fundamental limitations of the conventional PFM. It is believed that NC‐HEsFM can be extensively used in various ferroelectric or piezoelectric studies with providing substantially improved characterization performance. Meanwhile, the QTF‐based force detection makes NC‐HEsFM highly compatible for high‐vacuum and low‐temperature environments, providing ideal conditions for investigating the intrinsic ferroelectric phenomena with the possibility of achieving an atomically resolved ferroelectric characterization. Abstract : Non‐contact heterodyne electrostrain force microscopy (NC‐HEsFM) is introduced first for high‐resolution ferroelectric characterization. NC‐HEsFM breaks the fundamental limitations of piezoresponse force microscopy‐based nanoscale ferroelectric characterization by providing a brand‐new non‐contact yet non‐destructive, high‐resolution, non‐optical, electrostatic force effect‐eliminated, highly extreme environments compatible, and multi‐functional ferroelectric characterization solution, implying that NC‐HEsFM is an ideal measurement for nanoscale ferro/piezo‐electric studies.